ANALISIS DAN RANCANGAN MANAJEMEN PROSES BISNIS UNTUK LAYANAN PELANGGAN DI PT. PGAS TELEKOMUNIKASI NUSANTARA - Kemas Hasyim Azhari; Thomas Budiman; Rachmawaty Haroen; Verdi Yasin (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2021)
Business Process Management for corporate customer service is a comprehensive series of activities to define the types of products and services that will be the main needs of customers, so that the quality of service results can be planned and measured. Business process design is a framework for a core process that develops from a short-term and long-term business strategy, so that the business strategy will determine the pillars of the business that will be carried out. Serving the needs of customers and interested parties will be the main focus of a business process that will be carried out within the organization. The application of business process management is a method for identifying and evaluating a company's business and for finding out the current condition of the company in developing improvement programs that can be done through a descriptive process. The output and application of business process management are in the form of increasing the efficiency and productivity of the company in terms of cost and time as well as improving the quality of products and services produced, as well as mitigating business risks that may occur. Data collection methods, analysis methods, development methods, design design methods and testing methods are research methods that are used systematically so that it includes several activities for gradual improvement of the work process from previous conditions and increasing system reliability to obtain facts or principles from knowledge with how to issue register and perform root cause analysis with several impact assessments by quantitative analysis, heuristic design, simulation, flow analysis, pareto analysis and pick chart, queue, up to a systematic redesign to the process.